Karl Mannheim and Jean Floud: a false start for the sociology of education in Britain? (UCL Press, 2022)
Arriving in the UK after exile from Nazi Germany, Karl Mannheim taught sociology at the London School of Economics and then also at the London Institute of Education, where he was awarded a chair just a year before his untimely death in 1947. In his later writings and teaching, Mannheim argued that the sociology of education could make a crucial contribution to the new type of society he regarded as essential if the problems of liberal democracy were to be overcome, and the slide towards totalitarianism avoided. And the period immediately after his death was a key phase in the development and establishment of the sociology of education in Britain. Jean Floud, who took over teaching the subject at the Institute of Education after Mannheim's death, played a central role in this, but, while she had studied with him and served as his research assistant, she adopted a very different approach. This focused, in particular, on whether the existing structure and operation of educational institutions restricted social mobility. As a result of this change in focus, Mannheim's work had a very marginal role in the subsequent history of British sociology of education. In this article, I compare Mannheim's and Floud's competing conceptions of the character and role of the subdiscipline, and how these fared in later developments within the field.